2014
DOI: 10.1155/2014/854163
|View full text |Cite
|
Sign up to set email alerts
|

Urine Annexin A1 as an Index for Glomerular Injury in Patients

Abstract: Background. We recently demonstrated high urine levels of annexin A1 (ANXA1) protein in a mouse Adriamycin-induced glomerulopathy (ADG) model. Objective. To establish ANXA1 as a potential biomarker for glomerular injury in patients. Methods. A time-course study in the mouse ADG model, followed by renal tissues and urine samples from patients with various types of glomerular disorders for ANXA1. Results. Urinary ANXA1 protein was (1) detectable in both the ADG model and in patients except those with minimal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Ka et al found that the urinary ANXA1 was detectable as early as the stage of normoalbuminuria in diabetes mellitus patients. 25 Based on the previous studies and our data, we speculate that ANXA1 may enter the urine by either secretion from renal epithelial cells or direct release from immune cells. However, the results did not exclude the possibility that some of the excreted ANXA1 may be derived from glomerular filtration.…”
Section: Discussionsupporting
confidence: 61%
“…Ka et al found that the urinary ANXA1 was detectable as early as the stage of normoalbuminuria in diabetes mellitus patients. 25 Based on the previous studies and our data, we speculate that ANXA1 may enter the urine by either secretion from renal epithelial cells or direct release from immune cells. However, the results did not exclude the possibility that some of the excreted ANXA1 may be derived from glomerular filtration.…”
Section: Discussionsupporting
confidence: 61%
“…We found decreased levels of exosomal ANXA2 and ANXA1 in the MHA group. Annexins are a family of calcium-dependent phospholipid-binding proteins with anti-inflammatory activity [ 24 ]. Down-regulation of both ANXA1 and ANXA2 exosomal proteins is in agreement with a pro-inflammatory scenario in this clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous localization studies for AnxA1 have shown strong expression of the protein in renal epithelia and an increased abundance in response to renal injury (McKanna et al 1992, Araujo et al 2012, Ka et al 2014. These studies also suggested interstitial expres-sion of AnxA1, but its cellular source and function were unknown.…”
Section: Mergementioning
confidence: 94%